2011
DOI: 10.1097/qad.0b013e328348a7ac
|View full text |Cite
|
Sign up to set email alerts
|

Low-density lipoprotein receptor genotyping enhances the predictive value of IL28B genotype in HIV/hepatitis C virus-coinfected patients

Abstract: Variations in rs14158 are associated with SVR to Peg-IFN and RBV in HIV/HCV-coinfected patients harboring HCV genotype 1-4. LDLR and IL28B genotypes seem to have a synergistic effect on SVR. The combined use of LDLR and IL28B genotypes in routine clinical practice could enhance the predictive value of IL28B genotype alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 18 publications
2
35
0
Order By: Relevance
“…Considering a minor allele frequency of 0.3 and the ratio of high VL vs low VL, our study had an 80% power to detect an OR ¼ 2 (and 95% for OR ¼ 2.5) in genotypes 1 and 4 compared with 55% power to detect an OR ¼ 2 (and 78% for OR ¼ 2.5) in genotype 3. At least four prior studies reported data regarding HCV disease evolution and the genetic marker rs14158 of LDLR; 11,16,17,23 however, the main advantages of the current study are the in-depth genetic analysis including the most important genes of cholesterol pathways, a high coverage of LDLR gene with 33 SNPs in the region and the fact that no prior studies have studied an association of LDLR with pre-treatment VL. Three LDLR SNPs identified in this study related with HCV VL have been previously associated with SVR after treatment with interferon 12 (rs11672123, P ¼ 0.0067; rs1433099, P ¼ 0.0019; rs2569540, P ¼ 0.0044); all are located in introns or regulatory regions as promoter or 3 0 UTR.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Considering a minor allele frequency of 0.3 and the ratio of high VL vs low VL, our study had an 80% power to detect an OR ¼ 2 (and 95% for OR ¼ 2.5) in genotypes 1 and 4 compared with 55% power to detect an OR ¼ 2 (and 78% for OR ¼ 2.5) in genotype 3. At least four prior studies reported data regarding HCV disease evolution and the genetic marker rs14158 of LDLR; 11,16,17,23 however, the main advantages of the current study are the in-depth genetic analysis including the most important genes of cholesterol pathways, a high coverage of LDLR gene with 33 SNPs in the region and the fact that no prior studies have studied an association of LDLR with pre-treatment VL. Three LDLR SNPs identified in this study related with HCV VL have been previously associated with SVR after treatment with interferon 12 (rs11672123, P ¼ 0.0067; rs1433099, P ¼ 0.0019; rs2569540, P ¼ 0.0044); all are located in introns or regulatory regions as promoter or 3 0 UTR.…”
Section: Discussionmentioning
confidence: 86%
“…In the case of the West Nile virus, the exogenous addition of cholesterol can rescue interferon signaling and restrict viral replication. 15 Four prior studies reported data regarding HCV clinical evolution and genetic polymorphisms of LDLR; [11][12][13]16,17 nevertheless, the role of genetic polymorphisms in cholesterol metabolism in HCV replication is not clear. The main advantages of the present study are the in-depth genetic analysis of the most essential genes of the cholesterol transport pathway, a dense coverage of SNPs in LDLR gene and the fact that no prior studies have studied an association of LDLR with pre-treatment viral load (VL).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, a recent study reported the association between the IL-28B polymorphism and spontaneous recov- ery during coinfection with acute HCV hepatitis [46]. Although, the polymorphism of the low-density lipoprotein receptor was recently shown to enhance the predictive value of IL-28B polymorphism in HCV/HIV-coinfected patients [47]. Unfortunately, the lack of available samples did not allow us to study this new parameter.…”
Section: Core/ns2-specific Tgf-β+ T Cells (%) Core/ns2-specific Tgf-βmentioning
confidence: 96%
“…In addition, it is still recommended in settings where direct-acting antivirals (DAA) are not available due to financial restrictions [1]. Rates of sustained virological response (SVR) to Peg-IFN plus RBV vary considerably according to host and virus-related parameters, such as IL28B genotype, grade of liver damage, baseline plasma HCV RNA concentration, and HCV genotype [2,3].…”
Section: Introductionmentioning
confidence: 99%